Produção de biossurfactantes por Bacillus em meio com caldo de cana-de-açúcar - Oliveira, Carolina Zanini (2021)
Biosurfactants are molecules with a structure similar to chemically obtained surfactants, having the ability to mix phases of different polarities forming molecular aggregates or micelles and are also suitable for various industrial applications. The limitation of industrial production and large-scale commercialization of biosurfactants is due to the high cost of the substrates used for their production, which can reach up to 30% of the total cost. Thus, the search for a cost reduction strategy becomes essential to make production less expensive. The present work aims to produce a biosurfactant in media containing substrates of regional origin as inducers, using strains of Bacillus subtilis UFPEDA 16, B. subtilis UFPEDA 86 and B. pumilus and, subsequently, evaluate the compounds obtained for their stability and viability of use. Initially, tests were carried out to select the media containing sugarcane juice and avocado oil and sugarcane juice and residual oil. The cultures were tested using the three Bacillus strains and analyzed for the index of emulsification in vegetable oil every 24h, for a total of 96h of fermentation. The three strains produced good emulsifiers, with emphasis on B. pumilus, which showed the ability to emulsify up to 66.19 ± 0.67% in 48 h the media with avocado oil and residual oil. After the selection step, the kinetic assay of the strains that showed the best results was performed. In the growth kinetics, it was observed that the addition of avocado oil favored the growth of both Bacillus strains when compared to the medium containing only sugarcane juice as a carbon source. In the analysis of the biosurfactant production, the medium containing avocado oil favored its production, being possible to reach percentages of emulsification of 51.09 ± 4.24% for the B. pumilus strain and 49.98 ± 2.10% for the strain B. subtilis UFPEDA 16, both within 24 h of fermentation. For the strain results, the highest reduction percentages were obtained in the media without the use of oil with 29.21%, in 24 h, for B. subtilis UFPEDA 16 and 28.89%, in 12h, for B. pumilus. The cutting system (semi-continuous production) in the production of biosurfactants was used aiming at a possible increase to industrial scale. The experiments were carried out in three different percentages of cuts (40, 60 and 80%) and evaluated for the capacity of bioproduct formation during the fermentation process. The highest amount of bioproduct obtained was 5.76 ± 0.56 g/L, in 48 h and at 40% cut. The highest percentage of emulsification obtained was 52.70 ± 4.50% in the first cut of 60%. In the other cuts, values of 49.22 ± 2.91% and 45.28 ± 1.39% were observed in the samples of 40% and 60%, respectively, in the period of 48h. In the stability tests, the trials carried out with cottonseed oil indicated good tolerance to the pH range from 2 to 10, different percentages of NaCl, high temperatures and the ability to maintain stable emulsions over a period of 96 h. All results obtained in the proposed means were considered satisfactory for possible application in various industrial sectors.